Impactos econômicos da participação da mulher no mercado detrabalho brasileiro: uma análise de equilíbrio geral - Kenia Barreiro de Souza (2015)
The womens participation in Brazilian labor market has increased remarkably in the last decades. According to the International Labor Offices estimates (ILO, 2015), in 1990 the female labor force participation was 47.6% and in 2013, 65.07% of women between 16 and 64 years old were active in the labor market. Moreover, increasingly, those who found jobs are the most qualified ones. Despite these changes, unemployment rates are still higher, the wages are lower, and the employment is highly concentrated in some sectors. In this context, this paper aims to evaluate the importance of womans work, and its growth, for the Brazilian economy. We use a Dynamic General Equilibrium Model for Brazil, with three main developments. First, we disaggregate the labor factor by gender and qualification. Secondly, we split the household income into four types: labor; capital; government transfers and other sources. Lastly, the unemployment rate can be calculated by gender, qualification and representative household. Three simulations were carried out, historical, decomposition, and forecast. The first two covers the period 2006-2013, using detailed observed data for the labor market. The last simulation projects the increase in female participation through augmented womens labor demand. Results showed that when analyzing the GDP composition, labor loses contribution between 2006 and 2013. However, at the same time, women's contribution to total labor factor increased from 34.71% to 42.38%. This increase reflects not only the increase in womens employment, but especially reveals its increasing contribution to the national income. Of the average growth of GDP, 31.17% was explained by changes in labor usage during the observed period, being 28.37% due to the increased use of high-skilled woman. Regardless the positive overall effect on the economy, for several sectors changes in labor composition produced negative effects, indicating that labor, as an input in production, may have been a constraint to the expansion of those sectors. In general, the positive impacts were concentrated in the sectors related to domestic demand, in which womens work with high qualification gained importance. Examples are clothing items and accessories, leather goods and footwear, perfumery, hygiene and cleaning and most service sectors. On the other side, the negative effects were concentrated in manufacturing sectors linked to exports and the services related to them. Forecasts for the period 2014-2030 shows that the increase in female participation simulated by increased xvii demand for womens labor causes a positive cumulative deviations in GDP in the order 1.61% by 2030. These results are consistent with previous literature, in which the expansion of services and womens labor market participation are directly related. While the service sector creates job opportunities for women, rising women's income stimulates the demand for services. This virtuous cycle was imperative to sustain growth and employment in Brazil between 2006 and 2013, and directed the positive results in the forecast simulation. In this sense, public policies that encourage womens labor market participation have the potential to generate positive effects on economic growth.